Migration and Agency in a Globalizing World Afro-Asian Encounters (International Political Economy Series,, 2018)
This book - through a collection of case studies covering Southern and East Africa, China, India, Japan, South Korea and Southeast Asia - offers insights into the nature of social exchanges between Africa and Asia. In the age of the 'Rise of the South', it documents the entanglements and the lived experiences of African and Asian people on the move. Divided into three parts, the authors look at Asians in Africa, Africans in Asia, and the 'connected histories' that the two share, which illuminate emerging and historical modalities of Afro-Asian human encounters. Cornelissen and Yoichi show how migrants activate multiple forms of transnational social capital as part of their survival strategies and develop complex relationships with host communities. .